Aceh Provincial Government's Food Security Policy to Facing Covid-19 Pandemic - Syahnaz Oriza Keumala; Eko Priyo Purnomo; Suswanta Suswanta; Paisal Akbar (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
The Covid-19 pandemic has a significant impact on all aspects of life, especially in this case, its impact on food security conditions. With the imposition of restrictions on activities between regions to minimize the spread of Covid-19, we must put an acceptable food security policy to realize areas that are maintained in food conditions. The purpose of this research is to find out what food security policies the Aceh Provincial government is implementing in the face of the Covid-19 pandemic. The research method used is the qualitative method with a descriptive approach. The data obtained from online media reports are then processed using the Nvivo 12 Plus software to display Aceh Province's current policy issues. This study's findings indicate that the food security conditions of districts/cities in Aceh Province are still classified as green zones, meaning districts/cities in Aceh Province are still classified as healthy food security conditions. Meanwhile, the policy issue present in Aceh Province shows that at the national reporting level, six problems arise, namely farmers, agriculture, health, food, programs, and governance. In contrast, there are issues on rice, farmer, community, government, food policy, program, land, and agriculture at the local level. Furthermore, carried out findings related to food security policies in Aceh province through two programs, namely the Aceh Food Independent Movement (Gampong) program and the Rice Planting Index Improvement Program, or what is known as the IP-300 program. This activity program has been carried out well by the city/district level government through various derivative programs that are in line with the objectives of the Aceh Province food security policy program.